Financial decision making : concepts, problems, & cases - Hampton, John J. (Reston, Virginia : Reston Pub. Co., 1979)
This edition continues the stress on the analytical aspects of problem solving. The chapters develop step-by-step approaches to guide the reader from basic concepts to increasingly sophisticated analyses. Primarily this edition emphasizes ways to master the theory and application of financial management.
Includes bibliographical references and index.
hza 29/11/2018
Loans
Keywords: Corporations